The role of digital literacy for poverty alleviation in Nigeria - Apata, Stella Bolanle (Yayasan Mitra Persada Nusantara, 2024)
The 21st century, digital technology has become an integral part of daily life, transforming the way people communicate, access information, and conduct business. Nigeria, like many other developing nations, is experiencing a digital revolution that holds immense promise for alleviating poverty. Digital literacy, defined as the proficiency in using digital technologies and navigating the online landscape, has emerged as a powerful tool in the context of poverty alleviation in Nigeria. This study delves into the critical role that digital literacy plays in addressing poverty and enhancing economic well-being within the Nigerian context. It sheds light on the multifaceted impact of digital literacy, emphasizing its influence on access to education, employment opportunities, and the empowerment of marginalized communities. The study also underlines the existing challenges and the need for effective policy interventions to bridge the digital divide, particularly in the context of a developing nation like Nigeria. By harnessing the potential of digital literacy, Nigeria can work towards not only reducing poverty but also fostering inclusive economic growth.